Feasibility of different maize varieties as silage in China (Bangladesh Journal of Botany, 2025)
In the present study, waxy maize varieties Jingkenuo 2000, Wannuo 2000, Shancainuo 1911, Jingkunuo 569 and silage maize variety Yayuqingzhu 26 were used as test materials to explore the feasibility as silage. The biomass yield per unit area, dry matter mass, and water content were analyzed to determine the optimum harvest period of silage. During the optimum harvest period, dry matter mass, crude protein, crude fat, neutral detergent fiber (NDF), and acid detergent fiber (ADF) of silage were determined. The comprehensive quality of ensilage was evaluated by using roughage quality grading index (GI). The optimum harvest period of silage was 45 days after pollination. The GI index of Wannuo 2000 was higher than Yayuqingzhu 26, which was grade 2. The content of crude fat was the highest (78.35 g/kg). NDF and ADF were relatively lower, reaching 331.32 and 148.36 g/kg. In conclusion, Wannuo 2000 can be used to make silage.Bangladesh J. Bot. 54(1): 171-174, 2025 (March)